Budesonide–formoterol (inhalation powder) in the treatment of COPD - Ceylan, Erkan (Dove Medical Press, 2006)
The budesonide–formoterol dry powder inhaler (Symbicort(®) Turbuhaler(®) 160/4.5–640/18 μg/day) contains the long-acting β(2)-adrenoreceptor agonist formoterol and the inhaled corticosteroid budesonide. Two large, 12-month trials examined the effect of budesonide–formoterol 160/4.5 μg twice daily in COPD patients who met these criteria. The studies were identical, except one in which the patients had received oral prednisolone 30 mg/day and had inhaled formoterol 4.5 μg twice daily for 2 weeks before randomization. In terms of the FEV(1), budesonide–formoterol produced an effect greater than that of both budesonide alone and formoterol alone reported in previous studies. The combination was generally more effective than either of the components in terms of peak expiratory flow, symptoms, and exacerbations. These advantages of the combination over those of either budesonide alone or formoterol alone were quite consistent. Improving lung function and decreasing symptoms significantly, budesonide–formoterol combination therapy provides significant clinical improvements in COPD, despite the limited reversibility of impaired lung function in the disease.